Observation of the effectiveness of clinical indicators of cardiac shock wave therapy in patients with ischemic heart disease: A systematic review and meta-analysis - Wu, Xinze; Gu, Minghong; Ma, Yixuan; Song, Peiyu; Fang, Chenghu (Frontiers in Cardiovascular Medicine, 2023)
Objective Ischemic heart disease (IHD) has a high prevalence and mortality rate, imposing a heavy burden on patients and society, and there is still a need to optimize treatment options for IHD patients. Cardiac shock wave therapy (CSWT) is gaining popularity as a new treatment for IHD patients. The objective of this meta-analysis is to reassess the effects of CSWT on IHD patients in light of the limited number of clinical studies included in previously published reviews, inconsistent methodological quality, and unclear outcomes. Methods From database creation until September 1, 2022, 4 English databases and 3 Chinese databases were rigorously searched for any current controlled trials of CSWT for IHD. The Cochrane Risk of Bias Assessment Tool was used for methodological quality assessment. Review Manager v.5.4 software was used for meta-analysis. Results Nineteen published controlled trials totaling 1,254 subjects were included. Results showed that CSWT could enhance left ventricular function and myocardial viability, improve cardiac function and alleviate angina pectoris symptoms. The effects of CSWT and control groups on SAQ scores and exercise time were not statistically significant. Conclusion According to this systematic review and meta-analysis, CSWT may be beneficial for a number of IHD clinical indications. To verify these findings, more RCT studies with bigger sample numbers and higher methodological standards are required in the future.